NIEKTÓRE EKONOMICZNO-SPOŁECZNE ASPEKTY SPORU O SPRAWIEDLIWOŚĆ SPOŁECZNĄ - Suwalski, Andrzej (Wydział Prawa i Administracji UAM, 2002)
The article raises the issue o f the relationship between social justice and social structure. The analysis focuses upon the substance of relationship between social justice and welfare state. Additionally, some issues connected with the problems of labour market are discussed. Finally, the conclusions deal with the main topics o f the criticism of welfare state.
SELECTED SOCIO-ECONOMIC ASPECTS OF THE DEBATE OVER SOCIAL JUSTICE